2021
DOI: 10.1007/s40744-021-00397-7
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Arthritis: The Influence of Co-morbidities on Drug Choice

Abstract: Psoriatic arthritis (PsA) is associated with a higher burden of co-morbidities such as obesity, cardiovascular disease, non-alcoholic fatty liver disease, inflammatory eye disease, inflammatory bowel disease, skin cancer and depression compared to the general population. In the last 20 years, the therapeutic options for PsA have increased exponentially with the availability of tumor necrosis factor-alpha (TNF) inhibitors, interleukin (IL)-17 inhibitors, IL-12/23 inhibitors and Janus kinases/signal transducer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 191 publications
1
6
0
Order By: Relevance
“…As expected, we found that the number of comorbid diseases and age ≥60 years were associated with major polypharmacy in patients with PsA. Approximately 40% of patients with PsA have at least 3 comorbid diseases, and the high burden of comorbid conditions affects their therapeutic choices 29,30 . These comorbid conditions may also be treated with drugs that can cause polypharmacy.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As expected, we found that the number of comorbid diseases and age ≥60 years were associated with major polypharmacy in patients with PsA. Approximately 40% of patients with PsA have at least 3 comorbid diseases, and the high burden of comorbid conditions affects their therapeutic choices 29,30 . These comorbid conditions may also be treated with drugs that can cause polypharmacy.…”
Section: Discussionsupporting
confidence: 72%
“…Approximately 40% of patients with PsA have at least 3 comorbid diseases, and the high burden of comorbid conditions affects their therapeutic choices. 29,30 These comorbid conditions may also be treated with drugs that can cause polypharmacy. Moreover, age directly increases the risk of comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect is eliminated with Infliximab since it is dosed based on weight [ 72 , 123 ] Surgery For high-risk procedures, biologic therapy should be withheld 3–5 half-lives before surgeries [ 47 , 88 ] Biologics may be restarted after surgery if there is no evidence of infection and once healing is satisfactory [ 47 , 88 ] IBD Patients with a history of concomitant IBD might benefit from monoclonal TNFi and IL-12/23i since they are effective in IBD. Moreover, IL-23i, and JAKi are suggested to be used in patients with PsA and IBD [ 72 , 122 ] IL-17i are not used in patients with active IBD [ 89 , 128 ] Decisions regarding optimal therapeutic agent should be discussed with a gastroenterologist [ 122 ] Pregnancy and lactation Rheumatologists are expected to be familiar with drug safety during pregnancy and lactation to ensure that the disease is well controlled and to minimize the risks to both the mother and the infant. However, since the data regarding this field are derived from case reports, small series, and observational studies only, this area is still challenging to the treating clinicians The decision to initiate biologic therapy and treatment option should be determined on an individual basis based on risk management plans.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with LTBI should be treated with anti-TB treatment at least 1 month before initiating biologic therapy and are to be monitored every 3 months during the treatment course [ 47 , 88 , 96 – 98 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation